Balloon-Assisted Tracking to Overcome Radial Spasm during Transradial Coronary Angiography: A Case Report - N. J. W. Verouden; F. Kiemeneij (Case Reports in Cardiology)
Spasm of the radial artery is the most important cause of failure to perform coronary angiography via the transradial approach. Spasmolytic cocktail may prevent radial artery spasm but is relatively contraindicated in patients with aortic stenosis or diminished left ventricular function. In this case report we describe a recently published technique to overcome severe radial spasm during transradial coronary angiography in a patient with moderate aortic valve stenosis.